Impact of Nutrition on Enhanced Recovery After Surgery (ERAS) in Gynecologic Oncology - Bisch, Steven (Nutrients, 2019)
Enhanced recovery after surgery (ERAS) pathways aim to improve surgical outcomes by applying evidence-based practices before, during, and after surgery. Patients undergoing surgery for gynecologic malignancies are at high risk of complications due to population, patient, disease, and surgical factors. The nutritional status of the patient provides the foundation for recovery after surgery, and opportunities to optimize outcomes exist from the first patient assessment to the early days after surgery. This review highlights the importance of nutritional assessment and intervention during the pre-operative and post-operative periods in the context of ERAS in gynecologic oncology surgery. The emerging role of immunonutrition, carbohydrate loading, and the importance of individualized care are explored. Evidence from studies in gynecologic oncology is presented, where available, and extrapolated from colorectal and other cancer surgery trials when applicable.